Analysis of the Reasons for the High Turnover Rate of Hotel Staff and the Countermeasures-A case study of Yangzhou Shangri-La Hotel - Jiang, Yue (2020)
This study attempts to determine the relationship between the demographic factors such as gender, education, age and employment factors such as wage, position, tenure in the hospitality industry on the employee turnover intention of employees working in Shangri-La hotel in Yangzhou, China. Wenjuanxing, an online survey tool, was used to design the questionnaire survey. Distribution of the questionnaire began on 3 August,2020 and ended on 12 August,2020. I was being able to collected 123 responses from employees holding various positions in the Shangri-La hotel. In the data analysis part, by means of SPSS, independent samples t-test, one-way ANOVA was applied to test the hypotheses as well as for determining the relationship between several factors and employee turnover intention. The study results indicated that several demographic and human capital characteristics are determinants for employee turnover intentions working in the Shangri-La hotel. Differences between gender in terms of education level, position and wage in the Shangri-La hotel were not found in this study.